2010
DOI: 10.1007/s10803-010-0968-0
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: The Training and Assessment of Relational Precursors and Abilities (TARPA): A Preliminary Analysis

Abstract: The TARPA (Training & Assessment of Relational Precursors & Abilities) is a recently developed computer-based protocol for the assessment of a progression of key domains of responding critical to the development of generative language. In the current pilot study, five children with autism were assessed using the TARPA and their score on this protocol was correlated with ratings on the Vineland Adaptive Behavior Scales. Findings showed a statistically significant correlation. This and other features of TARPA pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 8 publications
3
22
0
2
Order By: Relevance
“…Results showed (i) a strong and significant correlation between TARPA performance and PLS-4 full-scale and subscales and (ii) evidence to support the hierarchical structuring of the TARPA. These findings support those of Moran et al (2010) by providing further evidence of the link between derived relational responding and language as well as by further demonstrating the utility of the TARPA as a method for assessing the former.…”
Section: Training and Assessment Of Relational Precursors And Abilitisupporting
confidence: 81%
See 4 more Smart Citations
“…Results showed (i) a strong and significant correlation between TARPA performance and PLS-4 full-scale and subscales and (ii) evidence to support the hierarchical structuring of the TARPA. These findings support those of Moran et al (2010) by providing further evidence of the link between derived relational responding and language as well as by further demonstrating the utility of the TARPA as a method for assessing the former.…”
Section: Training and Assessment Of Relational Precursors And Abilitisupporting
confidence: 81%
“…Overall then, this pattern of results was consistent with the RFT perspective that derived relational responding is the key process involved in language. Lastly, Moran et al (2010) also showed some differences in performance based on stimulus modality. For instance, a number of participants showed weaker responding on sections involving exclusively auditory stimuli than on sections involving at least some visual stimuli, irrespective of the strength of their overall performance.…”
Section: Training and Assessment Of Relational Precursors And Abilitimentioning
confidence: 93%
See 3 more Smart Citations